Pengaruh Pengembangan Karir, Budaya Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Aditya Mandiri Sejahtera di Kota Kendari - Rahmika, Rahmika; Abbas, Bakhtiar; Lisapaly, David C.E.; Asraf, Asraf (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
Human resource management is a crucial factor in achieving organizational goals, both in terms of profitability and company survival. In a specific context, PT. Aditya Mandiri Sejahtera faces challenges in career development, work culture, and work motivation that have implications for employee performance. This study seeks to fill the knowledge gap by analyzing the effect of career development, work culture, and work motivation on employee performance. The research method used is quantitative with a cross sectional study approach. The sampling technique uses a census and a sample size of 32 respondents. The results showed that simultaneously, the variables of career development, work culture, and work motivation had a positive and significant effect on employee performance. However, partially, career development has no significant effect, while work culture and work motivation have a positive and significant effect. The implications of this study indicate that improvements in work culture and work motivation can significantly improve employee performance, although career development requires a more comprehensive approach.